Preparation method of ultrafine-grain spherical lithium iron phosphate and application thereof

CN122977343APending Publication Date: 2026-10-27银贮(阜阳)科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611417926.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]然而,在超细化磷酸铁锂材料的制备及应用过程中仍存在一定限制

Benefits of technology

(1)本发明通过干法颗粒细化及球形化处理,使初代磷酸铁锂形成一次颗粒粒度D50≤100nm的超纳米球形前驱体,并结合流化汽相包覆提高碳层在颗粒表面的均匀性,有利于形成较均匀的碳包覆层并保持纳米尺度的圆整颗粒形貌,从而改善材料的倍率性能和低温性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977343A_ABST
    Figure CN122977343A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of superfine-crystal spherical lithium iron phosphate and application thereof, and relates to the technical field of lithium battery material preparation. 50 The method mixes iron source, lithium source, phosphorus source and first carbon source to carry out wet grinding until the particle size D 50 ≤100nm of the slurry is obtained; the slurry is spray-dried and subjected to first-time sintering in an inert atmosphere to obtain primary lithium iron phosphate; dry granulation and spheroidization are carried out on the lithium iron phosphate to obtain superfine-nano spherical precursor with a particle size D 50 ≤100nm; the precursor is placed in a fluidization atmosphere; second carbon source is heated and evaporated or gas-assisted atomized and then delivered to the fluidization atmosphere to contact the surface of the precursor to carry out fluidization coating; and second-time sintering is carried out to obtain superfine-crystal spherical lithium iron phosphate. The obtained material is used for wet electrode preparation, which is beneficial to keeping the particle morphology and carbon coating structure, and improving the rate performance and low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery material preparation technology, and in particular to a method for preparing ultrafine crystalline spherical lithium iron phosphate and its application. Background Technology

[0002] Lithium iron phosphate (LiFePO4) is a widely used cathode material for lithium-ion batteries, characterized by good thermal stability, high safety performance, long cycle life, and low cost. However, due to the inherently low electronic conductivity and lithium-ion diffusion rate of lithium iron phosphate, its rate performance and low-temperature performance are still insufficient, affecting battery capacity retention in high-rate charge / discharge and low-temperature environments.

[0003] Previously, to improve the electrochemical performance of lithium iron phosphate materials, mainstream strategies typically involved reducing particle size, optimizing particle morphology, and applying carbon coating to enhance electron transport capabilities and lithium-ion diffusion efficiency. Among these, ultrafine lithium iron phosphate, due to its ability to shorten lithium-ion transport paths and improve electrode reactivity, has gradually become an important technological direction for improving the rate performance and low-temperature performance of lithium iron phosphate.

[0004] However, certain limitations remain in the preparation and application of ultrafine lithium iron phosphate materials. On the one hand, during precursor preparation, the high viscosity of the slurry system makes further particle refinement susceptible to agglomeration and dispersion difficulties, hindering the acquisition of uniform and stable ultrafine particle structures. On the other hand, carbon coating at the ultrafine particle scale leads to increased particle surface area and reduced carbon source distribution uniformity, resulting in localized insufficient carbon coating or carbon enrichment, affecting the material's electron transport performance and structural stability. Furthermore, when ultrafine lithium iron phosphate is applied to wet electrode preparation, the reduced particle size and increased specific surface area easily affect the dispersion stability and flow properties of the electrode slurry, leading to increased slurry viscosity, exacerbated agglomeration, and further impacting electrode coating uniformity and battery performance consistency.

[0005] Therefore, how to improve the uniformity of carbon coating and enhance its processing adaptability in wet electrode preparation while achieving ultrafine and spherical lithium iron phosphate is an urgent problem to be solved. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the technical problem this invention aims to solve is to provide a method for preparing ultrafine spherical lithium iron phosphate and its application. This method achieves both ultrafine and spherical lithium iron phosphate while improving the uniformity of carbon coating and enhancing its processing adaptability in wet electrode fabrication. To solve the above technical problem, this invention provides the following technical solution: A first aspect of the present invention relates to a method for preparing ultrafine crystalline spherical lithium iron phosphate, comprising the following steps: S1. Mix the iron source, lithium source, phosphorus source and the first carbon source and perform wet grinding until the primary particle size D in the resulting slurry is reached. 50 The slurry obtained from grinding is spray-dried and then sintered for the first time under an inert atmosphere to obtain primary lithium iron phosphate with a wavelength of 300-500 nm. S2. The primary lithium iron phosphate is subjected to particle refinement and spheroidization under dry processing conditions to obtain a primary particle size D. 50 Ultra-nano spherical precursors ≤100nm; S3. The ultra-nano spherical precursor is placed in a fluidized atmosphere, and the second carbon source is heated and evaporated or atomized with gas and then transported to the fluidized atmosphere, so that the second carbon source comes into contact with the surface of the ultra-nano spherical precursor for fluidized coating, thereby obtaining a carbon-coated ultra-nano spherical precursor. S4. The carbon-coated ultra-nano spherical precursor is sintered a second time to obtain ultrafine crystalline spherical lithium iron phosphate.

[0007] Further, in step S1, the iron source, lithium source, and phosphorus source are mixed in a ratio of Li / Fe molar ratio of 1.00 to 1.05 and Fe / P molar ratio of 0.960 to 0.980. The iron source includes one or more of ferric phosphate, ferrous oxalate, and ferric oxide. The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium oxalate, and lithium dihydrogen phosphate. The phosphorus source includes one or more of iron phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.

[0008] Furthermore, in step S1, the first carbon source includes one or more of glucose, sucrose, starch, and citric acid; The amount of the first carbon source added is 5% to 12% of the mass of the iron source; The temperature of the first sintering is 550-650℃, and the holding time is 2-6 hours.

[0009] Furthermore, in step S2, the particle refinement and spheroidization process is carried out using a dry fluidization process; The fluidizing gas pressure for the dry fluidization process is 0.1–0.5 MPa, the processing speed is 1000–10000 rpm, and the processing time is 1–5 h.

[0010] Furthermore, in step S3, the ultra-nano spherical precursor is placed in a fluidized bed coating device, and the fluidized atmosphere is a nitrogen atmosphere with a fluidized nitrogen pressure of 0.1–0.3 MPa. When the second carbon source is a liquid carbon source, the second carbon source is heated and evaporated to form carbon source vapor, and then transported to the fluidized coating device under the action of nitrogen carrier gas; When the second carbon source is a solid carbon source, the second carbon source is prepared into a carbon source liquid and heated. The carbon source liquid is transported through a feed pump and atomized with gas under high pressure nitrogen. The atomized carbon source liquid is then sprayed into the fluidized coating device. The pressure of the nitrogen carrier gas or high-pressure nitrogen is 0.1 to 0.5 MPa, and the speed of the feed pump is 10 to 50 rpm.

[0011] Furthermore, the second carbon source includes one or more of glucose, sucrose, citric acid, ethanol, asphalt, resin, polyvinylpyrrolidone, and polyethylene glycol.

[0012] Furthermore, in step S4, the second sintering temperature is 700–800°C, the holding time is 5–15 h, and the sintering atmosphere is an inert atmosphere.

[0013] A second aspect of the present invention relates to the application of ultrafine spherical lithium iron phosphate in the preparation of wet electrodes. Ultrafine spherical lithium iron phosphate is prepared by any of the above-mentioned preparation methods. The ultrafine spherical lithium iron phosphate, polyvinylidene fluoride and a conductive agent are added to N-methylpyrrolidone to form an electrode slurry. The electrode slurry is subjected to wet grinding and dispersion treatment. The ground and dispersed electrode slurry is then coated, dried and rolled to obtain a wet electrode.

[0014] Furthermore, the solid content of the electrode slurry is 45-55%, and the wet grinding and dispersion treatment is carried out using a ball mill disperser, with rubber balls as the grinding media, a grinding speed of 1000-5000 rpm, and a grinding time of 1-4 hours.

[0015] Furthermore, the electrode paste is coated and then dried and rolled, wherein the coating thickness is 50-100 μm, the drying temperature is 80-120℃, the drying time is 2-4 h, and the rolling pressure is 10-30 MPa.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves a primary particle size D of lithium iron phosphate by dry particle refinement and spheroidization. 50 The use of ultra-nano spherical precursors with a diameter of ≤100 nm, combined with fluidized vapor phase coating to improve the uniformity of the carbon layer on the particle surface, is beneficial for forming a more uniform carbon coating layer and maintaining the spherical morphology of nanoscale particles, thereby improving the rate performance and low-temperature performance of the material.

[0017] (2) The present invention uses wet grinding and dispersion to prepare electrode slurry, which can reduce the damage to particle morphology and carbon coating layer caused by high-intensity airflow pulverization, and improve the fluidity, dispersion uniformity and coating process adaptability of electrode slurry. Attached Figure Description

[0018] Figure 1 This is a flowchart illustrating the preparation process of the ultrafine crystalline spherical lithium iron phosphate of this invention. Figure 2 The X-ray diffraction patterns of the first and second sintering products in Embodiment 1 of the present invention are shown below. Figure 3 The image is a scanning electron microscope image of the ultrafine spherical lithium iron phosphate prepared in Example 1 of the present invention at a magnification of ×30.0k. Figure 4 The image is a scanning electron microscope image of the ultrafine spherical lithium iron phosphate prepared in Example 1 of the present invention at a magnification of ×20.0k. Figure 5 This is a transmission electron microscope image of the ultrafine spherical lithium iron phosphate obtained in Embodiment 1 of the present invention. Figure 6 The 0.2C charge-discharge curves of lithium iron phosphate prepared in Example 1 and Comparative Example 1 of this invention are shown. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be described more clearly and completely below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0020] The term "ultrafine crystalline spherical lithium iron phosphate" in this invention refers to primary particle size D. 50 Lithium iron phosphate material with a particle size ≤100nm and a generally rounded shape when observed under a scanning electron microscope; the term "spherical" in this invention includes spherical and near-spherical shapes.

[0021] In this invention, a dry particle spheroidizer (VSN) is used to cause collisions and shearing of primary lithium iron phosphate particles under dry fluidization conditions to achieve particle refinement and spheroidization; a fluidized bed coating device (LC) is used to bring a heated and vaporized second carbon source into contact with the ultra-nano spherical precursor in the fluidized state and perform vapor phase coating.

[0022] In this invention, the Li / Fe molar ratio and Fe / P molar ratio are calculated based on the actual elemental content of each raw material, rather than solely on its ideal chemical formula. For example, when iron phosphate is used as both an iron and phosphorus source, the amounts of Fe and P are calculated based on the measured iron and phosphorus contents, respectively, and included in the total amount of Fe and P in the feeding system. Similarly, for lithium dihydrogen phosphate containing both Li and P, the measured amounts of Li and P are included in the total amount of the corresponding elements.

[0023] This invention employs different feeding methods depending on the physical state of the second carbon source. When the second carbon source is a liquid carbon source such as ethanol, the liquid carbon source is heated to evaporate and form carbon source vapor, which is then transported to the fluidized bed coating device using nitrogen as a carrier gas. When the second carbon source is a solid carbon source such as glucose, sucrose, citric acid, asphalt, resin, polyvinylpyrrolidone, or polyethylene glycol, the solid carbon source is first prepared into a carbon source liquid and heated, then transported to the feed end of the fluidized bed coating device via a feed pump. High-pressure nitrogen is used to atomize the carbon source liquid, forming droplets or aerosols that enter the fluidized atmosphere. The fluidized nitrogen keeps the ultra-nano spherical precursor in a fluidized and dispersed state, and the carbon source vapor or atomized carbon source liquid contacts the precursor surface. Subsequently, a second sintering process is used to pyrolyze and carbonize the second carbon source distributed on the particle surface, forming a carbon coating layer.

[0024] Unless otherwise stated, all solid contents mentioned in the examples are by weight percentage; all pressure units are in MPa; PVDF-5130 is polyvinylidene fluoride binder, SUPER Li is conductive agent, and NMP is N-methylpyrrolidone.

[0025] Example 1: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Iron phosphate, lithium carbonate, and glucose (as the first carbon source) are mixed according to a Li / Fe molar ratio of 1.03 and an Fe / P molar ratio of 0.968, wherein the amount of glucose added is 10% of the mass of the iron source; pure water is added to prepare a slurry with a solid content of 40%, and wet grinding is performed until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 550°C for 4 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0026] Step S2: The primary lithium iron phosphate obtained in step S1 is added to a dry particle spherical processor and processed for 5 hours under fluidized air pressure of 0.2 MPa and rotor speed of 5000 rpm. This allows the particles to collide and shear under dry conditions, resulting in primary particle size D. 50 It is an 80nm ultra-nano spherical precursor.

[0027] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.2 MPa. Use glucose as the second carbon source, prepare it into a carbon source liquid with a solid content of 50%, heat it to 200°C, and deliver it through a feed pump. Under the action of high-pressure nitrogen at a pressure of 0.3 MPa, perform gas-assisted atomization. Spray the atomized carbon source liquid into the fluidized bed coating device with a feed pump speed of 15 rpm and a coating time of 1 h to obtain carbon-coated ultra-nano spherical precursor.

[0028] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 720°C for 10 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0029] An application of ultrafine crystalline spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine crystalline spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 50%; wet grinding and dispersion for 2 hours at 2000 rpm using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 80 μm, drying at 105 °C for 3 hours, and roll forming under a pressure of 12 MPa to obtain a wet-process electrode.

[0030] Example 2: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Iron oxide, lithium dihydrogen phosphate, and sucrose (as the first carbon source) are mixed according to a Li / Fe molar ratio of 1.04 and a Fe / P molar ratio of 0.965, wherein the amount of sucrose added is 6% of the mass of the iron source; pure water is added to prepare a slurry with a solid content of 35% and wet-milled until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 650°C for 2 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0031] Step S2: Add the primary lithium iron phosphate obtained in step S1 to a dry particle spherical processor and process it for 3 hours under the conditions of fluidized air pressure of 0.3 MPa and rotor speed of 8000 rpm to obtain primary particle size D.50 It is a 60nm ultra-nano spherical precursor.

[0032] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.15 MPa. Use polyethylene glycol as the second carbon source, prepare it into a carbon source liquid with a solid content of 40%, heat it to 180°C, and deliver it through a feed pump. Under the action of high-pressure nitrogen at a pressure of 0.4 MPa, perform gas-assisted atomization. Spray the atomized carbon source liquid into the fluidized bed coating device with a feed pump speed of 30 rpm and a coating time of 0.5 h to obtain carbon-coated ultra-nano spherical precursor.

[0033] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 740°C for 8 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0034] An application of ultrafine spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 55%; wet grinding and dispersion for 3 hours at 1000 rpm using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 60 μm, drying at 95°C for 2 hours, and roll forming under a pressure of 15 MPa to obtain a wet-process electrode.

[0035] Example 3: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Ferrous oxalate, ammonium dihydrogen phosphate, lithium carbonate, and starch as the first carbon source are mixed according to a Li / Fe molar ratio of 1.02 and a Fe / P molar ratio of 0.970. The amount of starch added is 5% of the mass of the iron source. Pure water is added to prepare a slurry with a solid content of 30%, and wet grinding is performed until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 600℃ for 6 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0036] Step S2: Add the primary lithium iron phosphate obtained in step S1 to a dry particle spherical processor and process it for 1 hour under the conditions of fluidized air pressure of 0.5 MPa and rotor speed of 10000 rpm to obtain primary particle size D. 50 It is a 90nm ultra-nano spherical precursor.

[0037] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.25 MPa. Use sucrose as the second carbon source, prepare it into a carbon source liquid with a solid content of 45%, heat it to 150°C, and deliver it through a feed pump. Under the action of high-pressure nitrogen at a pressure of 0.4 MPa, perform gas-assisted atomization. Spray the atomized carbon source liquid into the fluidized bed coating device with a feed pump speed of 20 rpm and a coating time of 0.5 h to obtain carbon-coated ultra-nano spherical precursor.

[0038] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 740°C for 8 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0039] An application of ultrafine spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 45%; wet grinding and dispersion for 1 hour at 3000 rpm using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 75 μm, drying at 110°C for 2 hours, and roll forming under a pressure of 20 MPa to obtain a wet-process electrode.

[0040] Example 4: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Iron phosphate, lithium oxalate, and citric acid (as the first carbon source) are mixed according to a Li / Fe molar ratio of 1.035 and a Fe / P molar ratio of 0.968, wherein the amount of citric acid added is 12% of the mass of the iron source; pure water is added to prepare a slurry with a solid content of 45% and wet-milled until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 580°C for 5 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0041] Step S2: Add the primary lithium iron phosphate obtained in step S1 to a dry particle spherical processor and process it for 4 hours under the conditions of fluidized air pressure of 0.25 MPa and rotor speed of 8000 rpm to obtain primary particle size D. 50 It is a 50nm ultra-nano spherical precursor.

[0042] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.2 MPa; use ethanol as the second carbon source, heat the ethanol to 100°C to evaporate it, and transport it to the fluidized bed coating device under the action of nitrogen carrier gas at a pressure of 0.1 MPa. The feed pump speed is 10 rpm, and the coating time is 2 h to obtain carbon-coated ultra-nano spherical precursor.

[0043] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 760°C for 10 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0044] An application of ultrafine crystalline spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine crystalline spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 50%; wet grinding and dispersion for 2 hours at 2000 rpm using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 80 μm, drying at 105 °C for 3 hours, and roll forming under a pressure of 24 MPa to obtain a wet-process electrode.

[0045] Example 5: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Mix iron phosphate, lithium carbonate, and sucrose as the first carbon source according to a Li / Fe molar ratio of 1.025 and an Fe / P molar ratio of 0.975, wherein the amount of sucrose added is 7% of the mass of the iron source; add pure water to prepare a slurry with a solid content of 35% and perform wet grinding until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 620°C for 4 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0046] Step S2: Add the primary lithium iron phosphate obtained in step S1 to a dry particle spherical processor and process it for 4.5 hours under the conditions of fluidized air pressure of 0.25 MPa and rotor speed of 5500 rpm to obtain primary particle size D. 50 It is a 75nm ultra-nano spherical precursor.

[0047] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.25 MPa. Use resin as the second carbon source, prepare it into a carbon source liquid with a solid content of 60%, heat it to 200°C, and deliver it through a feed pump. Under the action of high-pressure nitrogen at a pressure of 0.3 MPa, perform gas-assisted atomization. Spray the atomized carbon source liquid into the fluidized bed coating device with a feed pump speed of 40 rpm and a coating time of 2.5 h to obtain carbon-coated ultra-nano spherical precursor.

[0048] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 720°C for 12 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0049] An application of ultrafine spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 48%; wet grinding and dispersion at 2500 rpm for 2.5 h using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 100 μm, drying at 120 °C for 1.5 h, and roll forming under a pressure of 26 MPa to obtain a wet-process electrode.

[0050] Example 6: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Iron oxide, lithium dihydrogen phosphate, and glucose (as the first carbon source) are mixed according to a Li / Fe molar ratio of 1.04 and an Fe / P molar ratio of 0.978, wherein the amount of glucose added is 9% of the mass of the iron source; pure water is added to prepare a slurry with a solid content of 40%, and wet grinding is performed until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 560°C for 4 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0051] Step S2: Add the primary lithium iron phosphate obtained in step S1 to a dry particle spherical processor and process it for 4 hours under the conditions of fluidized air pressure of 0.35 MPa and rotor speed of 7000 rpm to obtain primary particle size D. 50 It is a 90nm ultra-nano spherical precursor.

[0052] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.2 MPa. Use asphalt as the second carbon source, prepare it into a carbon source liquid with a solid content of 40%, heat it to 120°C, and transport it through a feed pump. Under the action of high-pressure nitrogen at a pressure of 0.35 MPa, perform gas-assisted atomization. Spray the atomized carbon source liquid into the fluidized bed coating device with a feed pump speed of 35 rpm and a coating time of 1.5 h to obtain carbon-coated ultra-nano spherical precursor.

[0053] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 740°C for 10 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0054] An application of ultrafine spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 52%; wet grinding and dispersion for 3 hours at 1500 rpm using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 85 μm, drying at 85°C for 4 hours, and roll forming under a pressure of 30 MPa to obtain a wet-process electrode.

[0055] Example 7: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Ferrous oxalate, ammonium dihydrogen phosphate, lithium carbonate, and citric acid (as the first carbon source) are mixed according to a Li / Fe molar ratio of 1.045 and a Fe / P molar ratio of 0.970. The amount of citric acid added is 7% of the mass of the iron source. Pure water is added to prepare a slurry with a solid content of 50%, and wet grinding is performed until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 600°C for 6 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0056] Step S2: Add the primary lithium iron phosphate obtained in step S1 to a dry particle spherical processor and process it for 2 hours under the conditions of fluidized air pressure of 0.45 MPa and rotor speed of 9000 rpm to obtain primary particle size D. 50 It is a 100nm ultra-nano spherical precursor.

[0057] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.2 MPa. Use polyvinylpyrrolidone as the second carbon source, prepare it into a carbon source liquid with a solid content of 55%, heat it to 180°C, and deliver it through a feed pump. Under the action of high-pressure nitrogen at a pressure of 0.2 MPa, perform gas-assisted atomization. Spray the atomized carbon source liquid into the fluidized bed coating device with a feed pump speed of 25 rpm and a coating time of 1 h to obtain carbon-coated ultra-nano spherical precursor.

[0058] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 720°C for 8 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0059] An application of ultrafine spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 50%; wet grinding and dispersion at 1000 rpm for 4 h using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 90 μm, drying at 100 °C for 2.5 h, and roll forming under a pressure of 24 MPa to obtain a wet-process electrode.

[0060] Example 8: This embodiment provides a method for preparing ultrafine-grained spherical lithium iron phosphate and its application in the preparation of wet-process electrodes. The method for preparing ultrafine-grained spherical lithium iron phosphate includes the following steps: Step S1: Iron phosphate, lithium oxalate, and starch as the first carbon source are mixed according to a Li / Fe molar ratio of 1.03 and a Fe / P molar ratio of 0.969, wherein the amount of starch added is 8% of the mass of the iron source; pure water is added to prepare a slurry with a solid content of 45% and wet-milled until the primary particle size D is reached. 50 The slurry was spray-dried and the dried powder was kept at 620°C for 5 hours under a nitrogen atmosphere to obtain the first-generation lithium iron phosphate.

[0061] Step S2: Add the primary lithium iron phosphate obtained in step S1 to a dry particle spherical processor and process it for 4 hours under the conditions of fluidized air pressure of 0.3 MPa and rotor speed of 5000 rpm to obtain primary particle size D. 50 It is an 80nm ultra-nano spherical precursor.

[0062] Step S3: Add the ultra-nano spherical precursor obtained in step S2 into a fluidized bed coating device with a fluidized nitrogen pressure of 0.2 MPa. Citric acid is used as the second carbon source, and it is prepared into a carbon source liquid with a solid content of 50% and heated to 100°C. It is then transported by a feed pump and atomized under high-pressure nitrogen at a pressure of 0.1 MPa. The atomized carbon source liquid is then sprayed into the fluidized bed coating device with a feed pump speed of 30 rpm and a coating time of 1.5 h to obtain carbon-coated ultra-nano spherical precursor.

[0063] Step S4: The carbon-coated ultra-nano spherical precursor obtained in step S3 is kept at 760°C for 5 hours under a nitrogen atmosphere to obtain ultrafine crystalline spherical lithium iron phosphate.

[0064] An application of ultrafine spherical lithium iron phosphate in the preparation of wet-process electrodes includes: adding the ultrafine spherical lithium iron phosphate obtained in step S4, PVDF-5130, and SUPER Li to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 55%; wet grinding and dispersion for 1 hour at 4000 rpm using a ball mill disperser with rubber balls as the grinding medium; then coating with a thickness of 80 μm, drying at 105 °C for 3 hours, and roll forming under a pressure of 18 MPa to obtain a wet-process electrode.

[0065] Comparative Example 1: This comparative example provides a method for preparing ultrafine spherical lithium iron phosphate and its application in the preparation of wet electrodes. The difference between this method and Example 1 is that the fluidization coating step S3 is not performed.

[0066] Comparative Example 2: This comparative example provides a method for preparing ultrafine spherical lithium iron phosphate and its application in the preparation of wet electrodes. The difference between this method and Example 1 is that the dry particle refinement and spheroidization treatment in step S2 is not performed.

[0067] Comparative Example 3: This comparative example provides a method for preparing ultrafine spherical lithium iron phosphate and its application in the preparation of wet electrodes. The difference between this method and Example 1 is that the dry particle refinement and sphericalization treatment and fluidized coating in steps S2 and S3 are not performed.

[0068] Comparative Example 4: This comparative example provides a method for preparing ultrafine spherical lithium iron phosphate and its application in the preparation of wet electrodes. The difference from Example 1 is that in step S4, the obtained ultrafine spherical lithium iron phosphate is subjected to air jet milling in a dry powder state. The milling pressure is 0.3 MPa, the classifying speed is 120 Hz, and the particle size D of the powder obtained after air jet milling is...50 It is 0.5μm.

[0069] Structural and morphological characterization; Figure 2 The X-ray diffraction patterns of the primary lithium iron phosphate obtained from the first sintering and the ultrafine-grained spherical lithium iron phosphate obtained from the second sintering in Example 1 are shown. Figure 2 It can be seen that the main diffraction peaks of the two sintering products correspond to the characteristic peaks of the lithium iron phosphate standard card shown in the figure.

[0070] Figure 3 and Figure 4 The surface morphology of the ultrafine-grained spherical lithium iron phosphate prepared in Example 1 is shown at different magnifications. Figure 3 and Figure 4 It is evident that the primary particle size of the obtained material is at the nanoscale, and the particles are spherical or near-spherical in shape. Figure 5 The carbon layer structure on the surface of the material particles obtained in Example 1 is shown. A carbon film can be observed on the surface of the LiFePO4 in the lower left black part, which indicates that a carbon coating layer is formed on the particle surface after vapor phase coating and second sintering.

[0071] Electrochemical performance testing; Wet electrodes prepared in Examples 1-8 and Comparative Examples 1-4 were used as positive electrodes, lithium metal sheets as negative electrodes, polypropylene membranes as separators, and 1 mol / L LiPF6 solution as electrolyte, wherein the volume ratio of solvents EC, DMC and EMC was 1:1:1, and CR2032 coin cells were assembled.

[0072] Within a voltage range of 2.0–3.75V, the capacitor was charged to 3.75V using a constant current and constant voltage method, and then discharged to 2.0V using a constant current method. Rate tests were performed in ascending order of 0.2C, 1C, 10C, and 20C, with each rate cycled three times and the average capacity value recorded. A low-temperature capacity test at -20℃ (1C) was also conducted, with three cycles and the average capacity value recorded. The low-temperature capacity retention rate was calculated as "1C capacity at -20℃ / 1C capacity at 25℃ × 100%". The test results are shown in Table 1.

[0073] Table 1 As shown in Table 1, the 0.2C capacity of the ultrafine spherical lithium iron phosphate obtained in Examples 1 to 8 is 160.1 to 163.1 mAh / g, the 20C capacity is 140.1 to 141.2 mAh / g, and the 1C capacity retention rate at -20℃ is 84.5% to 86.5%. Compared with Comparative Examples 1 to 4, Examples 1 to 8 show significant improvements in both high-rate capacity and low-temperature capacity retention.

[0074] Comparative Example 1 omitted the vapor phase coating step; Comparative Example 2 omitted the dry particle refinement and spheroidization steps; Comparative Example 3 omitted both of the above steps, and its high-rate capacity and low-temperature capacity retention were lower than those of Example 1; Comparative Example 4, after obtaining ultrafine spherical lithium iron phosphate, employed air jet milling, and its performance further declined. These results indicate that the combination of dry particle refinement and spheroidization, vapor phase coating, and avoiding subsequent high-intensity air jet milling is beneficial for maintaining particle morphology and carbon coating structure, and for improving the rate performance and low-temperature performance of the material.

[0075] Figure 6 The 0.2C charge-discharge curves of lithium iron phosphate prepared in Example 1 and Comparative Example 1 are shown, and the results correspond to the 0.2C capacity data listed in Table 1.

[0076] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.

Claims

1. A method for preparing ultrafine crystalline spherical lithium iron phosphate, characterized in that, Includes the following steps: S1. Mix the iron source, lithium source, phosphorus source and the first carbon source and perform wet grinding until the primary particle size D in the resulting slurry is reached. 50 The slurry obtained from grinding is spray-dried and then sintered for the first time under an inert atmosphere to obtain primary lithium iron phosphate with a wavelength of 300-500 nm. S2. The primary lithium iron phosphate is subjected to particle refinement and spheroidization under dry processing conditions to obtain a primary particle size D. 50 Ultra-nano spherical precursors ≤100nm; S3. The ultra-nano spherical precursor is placed in a fluidized atmosphere, and the second carbon source is heated and evaporated or atomized with gas and then transported to the fluidized atmosphere, so that the second carbon source comes into contact with the surface of the ultra-nano spherical precursor for fluidized coating, thereby obtaining a carbon-coated ultra-nano spherical precursor. S4. The carbon-coated ultra-nano spherical precursor is sintered a second time to obtain ultrafine crystalline spherical lithium iron phosphate.

2. The method for preparing ultrafine-grained spherical lithium iron phosphate according to claim 1, characterized in that, In step S1, the iron source, lithium source, and phosphorus source are mixed in a ratio of Li / Fe molar ratio of 1.00 to 1.05 and Fe / P molar ratio of 0.960 to 0.

980. The iron source includes one or more of ferric phosphate, ferrous oxalate, and ferric oxide. The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium oxalate, and lithium dihydrogen phosphate. The phosphorus source includes one or more of iron phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.

3. The method for preparing ultrafine-grained spherical lithium iron phosphate according to claim 1 or 2, characterized in that, In step S1, the first carbon source includes one or more of glucose, sucrose, starch, and citric acid. The amount of the first carbon source added is 5% to 12% of the mass of the iron source; The temperature of the first sintering is 550-650℃, and the holding time is 2-6 hours.

4. The method for preparing ultrafine-grained spherical lithium iron phosphate according to claim 1, characterized in that, In step S2, the particle refinement and spheroidization process is carried out using a dry fluidization process. The fluidizing gas pressure for the dry fluidization process is 0.1–0.5 MPa, the processing speed is 1000–10000 rpm, and the processing time is 1–5 h.

5. The method for preparing ultrafine-grained spherical lithium iron phosphate according to claim 1, characterized in that, In step S3, the ultra-nano spherical precursor is placed in a fluidized bed coating device, and the fluidized atmosphere is a nitrogen atmosphere with a fluidized nitrogen pressure of 0.1 to 0.3 MPa. When the second carbon source is a liquid carbon source, the second carbon source is heated and evaporated to form carbon source vapor, and then transported to the fluidized coating device under the action of nitrogen carrier gas; When the second carbon source is a solid carbon source, the second carbon source is prepared into a carbon source liquid and heated. The carbon source liquid is transported through a feed pump and atomized with gas under high pressure nitrogen. The atomized carbon source liquid is then sprayed into the fluidized coating device. The pressure of the nitrogen carrier gas or high-pressure nitrogen is 0.1 to 0.5 MPa, and the speed of the feed pump is 10 to 50 rpm.

6. The method for preparing ultrafine-grained spherical lithium iron phosphate according to claim 5, characterized in that, The second carbon source includes one or more of glucose, sucrose, citric acid, ethanol, asphalt, resin, polyvinylpyrrolidone, and polyethylene glycol.

7. The method for preparing ultrafine-grained spherical lithium iron phosphate according to claim 1, characterized in that, In step S4, the second sintering temperature is 700-800℃, the holding time is 5-15h, and the sintering atmosphere is an inert atmosphere.

8. An application of ultrafine-grained spherical lithium iron phosphate in the preparation of wet-process electrodes, characterized in that, Ultrafine spherical lithium iron phosphate is prepared by the preparation method according to any one of claims 1 to 7. The ultrafine spherical lithium iron phosphate, polyvinylidene fluoride and a conductive agent are added to N-methylpyrrolidone to form an electrode slurry. The electrode slurry is subjected to wet grinding and dispersion treatment. The ground and dispersed electrode slurry is then coated, dried and rolled to obtain a wet electrode.

9. The application according to claim 8, characterized in that, The electrode slurry has a solid content of 45-55%, and the wet grinding and dispersion treatment is carried out using a ball mill disperser with rubber balls as the grinding media. The grinding speed is 1000-5000 rpm, and the grinding time is 1-4 hours.

10. The application according to claim 8 or 9, characterized in that, The electrode paste is coated, dried, and rolled. The coating thickness is 50-100 μm, the drying temperature is 80-120℃, the drying time is 2-4 h, and the rolling pressure is 10-30 MPa.